Pengenalan Baca Tulis bagi Anak Usia Dini (THUFULA, 2015)
Chidhood Education is a stimulation for a time that full of important things happen in people life time. This is the beginning for the next step for every one in the future. Golden ages are 0 – 6 years old. This is the right time to give modal for them. The modals are reading and writing skills. If Teacher could practices the children with the right method, it will make the neutrons in their brain still alive till they grow up. There are nine rules for learning activities based on right-left brain activities with integrative and eleven Montessori steps to teach reading and writing skills for kid.